Corporate Scale, Financial Policy, and Tax Aggressiveness: A Panel Study of Southeast Asian Listed Firms - Junaidi, Ahmad; Yuniarti, Rina; Riswandi, Pedi (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study investigates the effects of profitability, leverage, and firm size on corporate tax avoidance among publicly listed food and beverage firms in two comparable emerging economies over a five-year observation period. It contributes to the tax avoidance literature by providing a cross-country, single-industry panel analysis that isolates structural firm attributes from short-term financial indicators within similar regulatory environments. Using purposive sampling and panel data regression with a Random Effect Model, the results reveal that profitability and leverage do not significantly influence tax avoidance, whereas firm size demonstrates a positive and significant association, indicating that larger firms possess greater structural capacity to engage in tax planning strategies. These findings imply that tax authorities should strengthen structural monitoring and regulatory scrutiny of large firms rather than focusing predominantly on financial performance metrics when addressing corporate tax avoidance.